Piano music of composers-minimalists in the teaching repertoire of higher music education - Anna Alexandrovna, Davydova; Stanislav Sergeevich, Lushnikov; Marina Viktorovna, Pereverzeva; Vladimirovich, Smirnov Alexander; Vladimirovich, Tsarev Denis (Opción, 2019)
The study is devoted to Piano music of composers-minimalists in the teaching repertoire of higher music education. The materials of the study are educational technologies and specific pedagogical methods, which encourage future music educators to appeal to and master the contemporary piano music. As a result, that there are many unresolved problems in this area that require theorist and practitioners’ attention. The results of the work allowed including minimalists’ pieces in the teaching repertoire and thus improving the professional training process of music educators and making them acquainted with the XX century music.